Brief and Evidence Review: Kombinasi Tretinoin, Klindamisin, dan Dexamethasone Topikal untuk Terapi Acne Vulgaris: Brief and Evidence Review: Kombinasi Tretinoin, Klindamisin, dan Dexamethasone Topikal untuk Terapi Acne Vulgaris - Yohanes Firmansyah; Sukmawati Tansil Tan (Yayasan Pendidikan Medika Indonesia, 2022)
Acne is one of the problems that often attacks young people with the result of impaired appearance and self-confidence in social relationships. Acne treatment itself becomes very difficult due to various factors that play a role together and are difficult to control. The new paradigm of pathophysiology or the course of acne has begun to be studied and researched in order to find types of drugs, either singly or in combination to provide the best outcome, and minimize the possibility of recurrence. Various drugs that have been circulating now are in the form of tretinoin, antibiotics, steroids, etc. Of the various types of drugs that are circulating and become the main choice for acne vulgaris treatment, there is a combination type that is considered quite optimal in the treatment of acne vulgaris in accordance with the new pathophysiological paradigm of acne vulgaris. This study discusses the elaboration of clinical evidence for the use of tretinoin, clindamycin, and dexamethasone as the main choice of topical therapy which together (combination) are used for the treatment of acne vulgaris. From the results of the literature search, it is known that the use of tretinoin, either alone or in combination, has good results in the treatment of acne vulgaris, but the use of combination with antibiotics such as clindamycin will increase the effectiveness of acne vulgaris treatment. On the other hand, this combination can reduce the possibility of antibiotic resistance. Clinical Practice Guidelines in Indonesia for the treatment of severe acne vulgaris, still adhere to the use of intralesional steroids. It is known that the use of intralesional steroids will have an impact on various side effects. Topical use of dexamethasone is considered quite wise because of its almost zero systematic effect, excellent local effect, and good effectiveness. At the end of the literature search, it is known that the combination cream of Tretinoin, Clindamycin, and Topical Dexamethasone for the Treatment of Acne Vulgaris is considered quite effective in terms of clinical, scientific evidence, and modern pathophysiology.